2021
DOI: 10.3390/ijms22147656
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OsERF83, a Vascular Tissue-Specific Transcription Factor Gene, Confers Drought Tolerance in Rice

Abstract: Abiotic stresses severely affect plant growth and productivity. To cope with abiotic stresses, plants have evolved tolerance mechanisms that are tightly regulated by reprogramming transcription factors (TFs). APETALA2/ethylene-responsive factor (AP2/ERF) transcription factors are known to play an important role in various abiotic stresses. However, our understanding of the molecular mechanisms remains incomplete. In this study, we identified the role of OsERF83, a member of the AP2/ERF transcription factor fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…OsGGPS , OsTPS3 , and OsTPS23 were upregulated four‐ to fivefold in T_CS, suggesting a role for terpenoids in DREB1a‐mediated stress tolerance. Jung et al ( 2021 ) found induction of OsTPS3 as part of the mechanism associated with improved drought tolerance in rice. Phenylpropanoid pathway genes OsCCR and OsC4H that encode cinnamoyl‐CoA reductase and cinnamate 4‐hydroxylase, respectively, were upregulated >6‐fold in T_CS (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OsGGPS , OsTPS3 , and OsTPS23 were upregulated four‐ to fivefold in T_CS, suggesting a role for terpenoids in DREB1a‐mediated stress tolerance. Jung et al ( 2021 ) found induction of OsTPS3 as part of the mechanism associated with improved drought tolerance in rice. Phenylpropanoid pathway genes OsCCR and OsC4H that encode cinnamoyl‐CoA reductase and cinnamate 4‐hydroxylase, respectively, were upregulated >6‐fold in T_CS (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Secondary metabolitesSeveral genes involved in secondary metabolite production were markedly upregulated in T_CS that include genes encoding geranylgeranyl pyrophosphate synthase (GGPS), terpene synthases (TPS), phenylpropanoid (lignin) pathway, and polyamine oxidase (PAO). OsGGPS, OsTPS3, and OsTPS23 were upregulated four-to fivefold in T_CS, suggesting a role for terpenoids in DREB1a-mediated stress tolerance Jung et al (2021). found induction of OsTPS3 as part of the mechanism associated with improved drought tolerance in rice.…”
mentioning
confidence: 84%
“…OsGGPS, OsTPS3 and OsTPS23 were upregulated 4 -5-fold in T_CS, suggesting a role for terpenoids in DREB1a mediated abiotic stress tolerance. Jung et al (2021) found induction of OsTPS3 as part of the mechanism associated with improved drought tolerance. Phenylpropanoid pathway genes, OsCCR and OsC4H that encode Cinnamoyl-CoA reductase and Cinnamate 4-hydroxylase, respectively, were upregulated > 6-fold in T_CS (Table 2).…”
Section: Secondary Metabolitesmentioning
confidence: 96%
“…In rice, Sub1A and SNORKEL1/2 modulate flooding tolerance via two different physiological mechanisms [ 60 , 61 , 62 , 63 ]. Overexpression of OsDREB1s , OsDREB2A , OsEREBP1 , OsERF48 , OsERF71 , OsLG3 , OsERF83 , OsERF101 , OsERF115 , and OsERF4a ( OsERF3 ) improved drought tolerance in rice, through activating the jasmonate and abscisic acid (ABA) signaling pathways or modulating root architecture [ 57 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. By contrast, OsEBP89 , OsERF109 , OsDERF1 , OsERF3, and OsAP2-39 negatively regulated rice drought tolerance [ 70 , 79 , 80 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%